Quality of UHT whole milk marketed in Pernambuco, Brazil - Silva, Amanda Thaís Ferreira; Sena, Diana Guiomar Ferreira; Silva, Daniel Dias; Souza, Thamyris Gracinda P. Khoury; Medeiros, Elizabeth Sampaio; Moura, Andrea Paiva Botelho Lapenda; Rolim, Amália Maria Queiroz; Peixoto, Thaíse Virgínia Freire Ramos; Mesquita, Amanda Rafaela Carneiro; Paiva, José Egito; et al. (Medicina Veterinária, 2021)
The objective of this study was to evaluate the physical-chemical properties and microbiological quality of Ultra-high temperature (UHT) whole milk marketed in Pernambuco state, Brazil. In total, 390 samples of UHT whole milk were purchased from commercial establishments located in the mesoregions of Pernambuco, and transported to the Laboratory of Meat and Milk Inspection at Federal Rural University of Pernambuco. The physical-chemical analyzes and the microbiological evaluations were carried out following specific legislation. All 13 brands tested met the determined physical-chemical standards. However, it was found that 105 (26.9%) samples were in disagreement with microbiological standardization. It is important to highlight the need of further development of integrated actions involving the inspection bodies and the processing plants, in order to adjust the product to the quality standards established in the legislation, respecting the rights and health of consumers.